2014
DOI: 10.1007/s10557-014-6538-5
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-Interacting Protein: Pathophysiology and Emerging Pharmacotherapeutics in Cardiovascular Disease and Diabetes

Abstract: The thioredoxin system, which consists of thioredoxin (Trx), nicotinamide adenine dinucleotide phosphate (NADPH) and thioredoxin reductase (TrxR), has emerged as a major anti-oxidant involved in the maintenance of cellular physiology and survival. Dysregulation in this system has been associated with metabolic, cardiovascular, and malignant disorders. Thioredoxin-interacting protein (TXNIP), also known as vitamin D-upregulated protein or thioredoxin-binding-protein-2, functions as a physiological inhibitor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 99 publications
2
80
1
Order By: Relevance
“…Importantly, our experiments with THP1 cells cultured under various HG/NG conditions revealed an association between persistent DNA-me triggered by prior history of HG exposure and enhanced TXNIP expression in response to HG in vitro. We, thus, speculate that transient hyperglycemic episodes during the EDIC Study would induce more TXNIP overexpression and cellular dysfunction in cases vs. controls because of TXNIP hypo-me, which is in line with the reported adverse cellular roles of TXNIP (43)(44)(45)48). This type of cellular response to episodic HG provides mechanistic information toward understanding the connections between persistent DNA hypo-me at TXNIP and its gene expression and hence, metabolic memory of diabetic complications.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Importantly, our experiments with THP1 cells cultured under various HG/NG conditions revealed an association between persistent DNA-me triggered by prior history of HG exposure and enhanced TXNIP expression in response to HG in vitro. We, thus, speculate that transient hyperglycemic episodes during the EDIC Study would induce more TXNIP overexpression and cellular dysfunction in cases vs. controls because of TXNIP hypo-me, which is in line with the reported adverse cellular roles of TXNIP (43)(44)(45)48). This type of cellular response to episodic HG provides mechanistic information toward understanding the connections between persistent DNA hypo-me at TXNIP and its gene expression and hence, metabolic memory of diabetic complications.…”
Section: Discussionsupporting
confidence: 66%
“…TXNIP expression is highly induced by HG in various cell types (46)(47)(48), which by inhibiting thioredoxin, subsequently causes oxidative stress and apoptosis. Recently, TXNIP up-regulation in the diabetic kidney was reported to be associated with changes in certain histone PTMs (49).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that Trx2 levels are reduced in the hearts of patients with DCM, and that Trx2 knock-out mice have a progressive decline in LV function leading to death by HF (Huang, et al, 2015). These effects may be related to the upregulation of TXNIP, which inhibits Trx2 (Chong, et al, 2014). In a mouse pressureoverload model of HF, TXNIP knock-out mice initially had reduced cardiac hypertrophy and preserved LV contractile reserve compared to their wild-type litter mates (Yoshioka, et al, 2012).…”
Section: Ketone Metabolismmentioning
confidence: 99%
“…Ubiquitously expressed and pro-apoptotic, TXNIP exerts its effect via inhibition of the antioxidant thioredoxin, but also has some thioredoxin-independent effects, 54 including direct inhibition of glucose uptake by GLUT1 55 , 56 through the transcriptional complex, MondoA:Mlx 57 . In both high dose STZ-induced T1D and ob/ob T2D mice, administration of a calcium channel blocker reduced the cardiac expression of TXNIP and cleaved caspases in vivo , 58 but it is not known if cardiac function was preserved.…”
Section: Oxidative Stress and Metabolic Dysfunction In Diabetic Camentioning
confidence: 99%